Sorption and Phase Associations of Chromate and Vanadate with Two Contrasting North Carolina Saprolites - Fatai O. Balogun; Hannah R. Peel; Robert E. Austin; Ibrahim G. Okunlola; David S. Vinson; Owen W. Duckworth; Matthew L. Polizzotto (Soil Systems)
Geogenic chromium (Cr) and vanadium (V) contamination of groundwater in the Piedmont region of North Carolina poses threats to public health. These contaminants are naturally derived from saprolite and aquifer materials, but geochemical variability in these materials makes it difficult to predict specific risks of Cr and V in well water. The objectives of this study were to (1) determine host phases of Cr and V in representative subsurface materials; (2) characterize contaminant binding parameters of chemically variable saprolites; and (3) examine the influence of saprolite chemistry on contaminant sorption, speciation, and phase associations. Isotherm experiments revealed that saprolite samples sorbed roughly an order of magnitude more V than Cr. Chemical extractions and synchrotron-based X-ray fluorescence showed that substantial Cr and V were bound with metal oxide/oxyhydroxides in native and Cr-and V-sorbed saprolites; however, electrostatically bound fractions were also present, representing potentially important sources of groundwater contamination. X-ray absorption-near-edge-structure spectroscopy indicated that sorbed Cr was found as reduced Cr(III), whereas sorbed V was dominated by the oxidized V(V) and intermediate V(IV) species. Results from this study could be used to help parameterize mechanistic models and improve prediction of the Cr and V contamination potential of shallow aquifers.